2019
DOI: 10.1016/j.jbo.2019.100220
|View full text |Cite
|
Sign up to set email alerts
|

Novel 3D-printed prosthetic composite for reconstruction of massive bone defects in lower extremities after malignant tumor resection

Abstract: Highlights Novel 3D-printed prosthetic composite represents an attractive option for reconstructing massive bone defects. Combination of bioceramics and/or vascularized fibula contribute to long-term stability of prosthesis. P-B reconstruction is recommended for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
0
19
0
2
Order By: Relevance
“…However, there is still a need for innovative reconstruction options, especially in young patients and locally advanced tumors of the upper limb. Lu et al have demonstrated good clinical results for the reconstruction of intercalary massive bone defects of the femur and tibia in sarcoma patients with 3D printed prostheses combined with beta-triacalcium phosphate bioceramics and/or vascularized fibulae [ 10 ], while Fan et al have reported good results of customized 3D printed titanium prostheses of the clavicle, scapula, and pelvis [ 2 ]. Our cases are the first that describe the results of 3D printed prostheses in the long bones of the upper extremity after resection of the entire affected bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a need for innovative reconstruction options, especially in young patients and locally advanced tumors of the upper limb. Lu et al have demonstrated good clinical results for the reconstruction of intercalary massive bone defects of the femur and tibia in sarcoma patients with 3D printed prostheses combined with beta-triacalcium phosphate bioceramics and/or vascularized fibulae [ 10 ], while Fan et al have reported good results of customized 3D printed titanium prostheses of the clavicle, scapula, and pelvis [ 2 ]. Our cases are the first that describe the results of 3D printed prostheses in the long bones of the upper extremity after resection of the entire affected bone.…”
Section: Discussionmentioning
confidence: 99%
“…A possible strategy to reduce the infection rate could be the use of a myocutaneous flap; the one most often used in literature is the vertical rectus abdominis myocutaneous flap, harvested from the ipsilateral or from the contralateral side [29,30]. Alternatively, the pedicle anterolateral flap can also be considered [31].…”
Section: Complicationsmentioning
confidence: 99%
“…Current biomaterials research seeks to identify alternative materials to metals and ceramics, especially for prosthetic and orthopaedic applications [1,2]. Much attention has been paid to polymer-ceramic composites and possible surface modification methods of ceramic fillers to increase their durability [3,4].…”
Section: Introductionmentioning
confidence: 99%